The Concept of Developing Teacher and Lecturer Professionalism in Educational Institutions in Serang Regency - Rohaemi; Muhammad Faruq Al-amini; Anis Fauzi; Ahmad Qurtubi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Teachers and lecturers are educational personnel who have an important role in improving quality in the world of education. Although both have differences in carrying out their duties at the educational level. However, they have the same goal of improving and educating the nation's children through their role as educators. This research uses a qualitative research method based on a systematic literature review known as a literature review. With this method, research subjects related to the concept of professional development of teachers and lecturers at educational institutions in Serang district can be explained more clearly and easily and convey the main points of the research. The research data sources were obtained from journals and articles and writings related to the research subject via mendeley.com, the publish or perish application and Google Scholar. So the research results show that becoming an educator is not an easy thing. However, when faced with obstacles and challenges, teaching staff are able to develop their abilities and knowledge. So this can improve skills and mastery of material through special training for educators, in order to achieve success in carrying out their role as educators.